Tri‐band bandpass filters using modified tri‐section stepped impedance resonator with improved selectivity and wide upper stopband. Issue 15 (1st December 2013) - Ghatak, Rowdra; Pal, Manimala; Sarkar, Pankaj; Aditya, Amit Kumar; Poddar, Dipak Ranjan
Abstract : This study presents tri‐band bandpass filters using two variant designs based on tri‐section stepped impedance resonators (SIR) to achieve passband selectivity. The passbands are centred about 2.4, 3.5 and 5.5 GHz, respectively. The first design pertains to an asymmetric stepped impedance stub‐loaded tri‐section SIR and the second one consists of embedded SIR. Both the techniques contribute in improving the selectivity by inserting transmission zero between first passband and second passband. With a simple extension of one of the input/output coupling feed lines transmission zeros are inserted between second and third passband. The filter exhibits a wide stopband till 10 GHz because of, cascading with the feed line, a low‐pass filter with upper cutoff at 6.4 GHz. The passband insertion loss is within 2 dB. The group delay excursion for both the developed filters for the three passband suggests linearity of phase. Fabricated prototypes for both the variants are realised with simulated and measured results in good agreement.